Введение в историю Греции [окончание, предисловие] - Бузескул, Владислав Петрович; Buzeskul, Vladislav Petrovich (Х. : Паровая типография и литография М. Зильберберг и С-вья., 1903)
Владислав Петрович Бузескул (1858-1931) - історик-античник, історіограф, академік АН СРСР (1922), академік НАНУ (1925). Обіймав посади приват-доцента та професора Харківського університету (1885—1924). Науково-літературна діяльність Бузескула дуже різноманітна, але головні праці його стосуються галузі давньогрецької історії. Декілька його робіт присвячені історії Харківського університету. Buzeskul Vladislav Petrovich (1858-1931), historian, historian, academician of the Academy of Sciences of the USSR (1922), Academician of the National Academy of Sciences (1925). He held the positions of assistant professor and professor of Kharkov University (1885-1924). Buzeskul ’s Scientific and literary activities are very diverse, but his main works are in the area of ancient Greek history. Several of his works are devoted to the history of the Kharkov University.
Keywords: введення в історію Греції; історія Греції; Бузольт, Георг